Ejecución presupuestal y calidad del gasto en la Municipalidad Provincial de Requena 2025 - Guevara Cardenas, Lenner Henry (2025)
The purpose of this research was to determine the relationship between budget execution and the quality of expenditure in the Provincial Municipality of Requena 2025. The study was of a basic, non-experimental design. The findings show that the budget execution variable is bad for 12.5% and 50.0% stated that it is good; in the quality of expenditure variable, 10.0% provided a response that it is bad and 45.0% stated that it is good. Furthermore, the chi square test showed a significance value of 0.000<0.05, indicating that there is a direct relationship between budget execution and quality of expenditure in the Provincial Municipality of Requena 2025.